NGS analysis of collagen type I genes in Polish patients with Osteogenesis imperfecta: a nationwide multicenter study - Sałacińska, Kinga; Pinkier, Iwona; Rutkowska, Lena; Chlebna-Sokół, Danuta; Jakubowska-Pietkiewicz, Elżbieta; Michałus, Izabela; Kępczyński, Łukasz; Salachna, Dominik; Wieczorek-Cichecka, Nina; Piotrowicz, Małgorzata; Chilarska, Tatiana; Jamsheer, Aleksander; et al. (Frontiers in Endocrinology, 2023)
Osteogenesis imperfecta (OI) is a rare genetic disorder of the connective tissue. It presents with a wide spectrum of skeletal and extra-skeletal features, and ranges in severity from mild to perinatal lethal. The disease is characterized by a heterogeneous genetic background, where about 85-90% of cases have dominantly-inherited heterozygous pathogenic variants located in the COL1A1 and COL1A2 genes. This paper present the results of the first nationwide study, performed on a large cohort of 197 Polish OI patients. Variants were identified using a NGS custom gene panel and MLPA assay. The following OI types were observed: 1 (42%), 2(3%), 3 (35%), and 4 (20%). Collagen type I pathogenic variants were reported in 108 families. Alterations were observed in α1 and α2 in 70% and 30% of cases, respectively. The presented paper reports 97 distinct causative variants and expands the OI database with 38 novel pathogenic changes. It also enabled the identification of the first glycine to tryptophan substitution in the COL1A1 gene and brought new insights into the clinical severity associated with variants localized in "lethal regions". Our results contribute to a better understanding of the clinical and genetic aspects of Osteogenesis imperfecta.